Two new Craspedophorus species (Coleoptera: Carabidae: Panagaeini) from the Philippines - Häckel, Martin; Anichtchenko, Alexandr (Zootaxa, 2015)
Two new species of the genus Craspedophorus Hope, 1838 from the Philippine Islands namely, C.luzonensis sp. nov. and C. kirschenhoferi sp. nov. are described and their affinities are discussed, illustrated and compared with related taxa. Craspedophorus luzonensis sp. nov., from Luzon, belongs to the “obscurus species group, whereas C. kirschenhoferi sp. nov., from Mindanao, stands isolated in the genus.